Desain Sistem Teknologi Tesla Coil Untuk Beban Lampu - Zuliyanto, Angga; Asy'ari, ST., MT, Hasyim Asy'ari, ST., MT (2017)
Tesla coil is a media generating high voltage with high frequency, so that with a small current is able to produce a large voltage, basically tesla coil will generate electrical waves or the electromagnetic waves that can affect the surrounding atoms around it that will cause electrical sparks like fireworks or like a flash of light. The purpose of this research is to design and create a series of system design technology tesla coil to the light load with an ideal distance. The method used is by using literature study, data collection, design tools, tool manufacture, testing and Data Analysis. windings used is the number 300 coil windings cross-sectional area of 0.5 mm2. This test uses the power supply voltage is 9 Volt, 10 Volt, 11 Volt and 12 Volt with massive transformer is 3 A, and lamps used in the test is to use a lamp with 8 watt light bulb brand. From all testing with voltage parameters are changed, there is a limit voltage, distance and magnitude of the magnetic field to power the lights. ie at a voltage of 9 and 10 volts, the light can only be lit in a radius of 15 cm, and the magnitude of the magnetic field that is 5,137 x 10-7 Tesla and 5,7 x 10-7 Tesla, the intensity of light is 13 and 19 Lux. but when the supply voltage 11 and 12 volts with a radius of 20 cm and with the magnitude of the magnetic field generated is 4,71 x 10-7 Tesla and 5,125 x 10-7 Tesla. lights can be lit with light intensity 13 and 20 lux. so there are limits the amount of magnetic field to turn on lights, namely between a magnitude of more than 4,275 x 10-7 Tesla to 4,71 x 10-7 Tesla.